2021
DOI: 10.3389/fphar.2021.590994
|View full text |Cite
|
Sign up to set email alerts
|

Qing-Yi Decoction in the Treatment of Acute Pancreatitis: An Integrated Approach Based on Chemical Profile, Network Pharmacology, Molecular Docking and Experimental Evaluation

Abstract: Background: Qing-Yi Decoction (QYD) is a classic precompounded prescription with satisfactory clinical efficacy on acute pancreatitis (AP). However, the chemical profile and overall molecular mechanism of QYD in treating AP have not been clarified.Methods: In the present study, a rapid, simple, sensitive and reliable ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS)-based chemical profile was first established. An integration strategy of network ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Several basic investigations have shown the molecular mechanisms of QYD in the treatment of SAP and associated distant organ damage. Wei et al's network pharmacology study demonstrated that QYD might attenuate pancreatic injury during SAP by inhibiting NF- κ B-mediated inflammatory response [ 10 ]. By suppressing intestinal sPLA2 expression, QYD dramatically reduced AP-induced intestinal barrier damage [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several basic investigations have shown the molecular mechanisms of QYD in the treatment of SAP and associated distant organ damage. Wei et al's network pharmacology study demonstrated that QYD might attenuate pancreatic injury during SAP by inhibiting NF- κ B-mediated inflammatory response [ 10 ]. By suppressing intestinal sPLA2 expression, QYD dramatically reduced AP-induced intestinal barrier damage [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…is added and simmered for an additional 0.5 h. Filter when hot, add Na 2 SO 4 ·10 H 2 O, blend the two filtrates, concentrate to 1 g/ml, sterile package, and store at 4°C for future use. The chemical profiles of QYD mapped using ultraperformance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry are presented in the previous study [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, further work is needed to study global metabolic changes in other species to fully elucidate the mechanisms by which YZD improves AD. Enhanced metabolomics technologies, such as targeted metabolomics, are required to detect metabolite biomarkers ( Wei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[58] The study found that the treatment of AP with QYD may be related to its anti-inflammatory effect. [58,59] It has a significant effect on the treatment of AP, [60] acute biliary pancreatitis (ABP), [61] and SAP. [62] Red peony root decoction Red peony root decoction is more effective than rhubarb alone for SAP patients, when the patient took it, the patients' total days of using antibiotics, enzyme inhibitors, and hospitalization costs were decreased.…”
Section: Huoxueqingyi Decoctionmentioning
confidence: 98%